Causes and effects of economic crises on the example of Republic of Croatia - Ergović, Ariana; Ivona Gambiraža (Oeconomica Jadertina, 2023)
Crisis represents an unforeseen and unwanted cycle which can be caused by a problem of health, political or financial nature. The crisis of 2008 was caused by the collapse of subprime mortgages, while the 2021 crisis was caused by the virus COVID-19. Looking retrospectively, the 1929 and the 2008 crisis have in common the fact that both governments knew what to do to fix it, but refused to do so. Therefore, when looking back at financial crises, many similarities can be found, which makes finding the solution of the problem easier. The difference can be found in 2021 crisis caused by pandemic which took on a global scale in a very short period of time and paralysed the world. Consequently, the approach to 2021 crisis differentiates from the 2008 financial crisis. Health had been put first which highly affected business results, and regardless of all the efforts, the isolation and the lack of people travelling took its toll. Croatian GDP in 2020 fell more than in the 2008 crisis which gives a slight idea of the galloping impact the health crisis had. Subsequently, the state intervention on the consumer pockets was crucial; to have a population feel its intensity as little as possible. The main goal of this paper is to compare the 2008 financial crisis and the 2021 health crisis, with a focus on observing differences and similarities between stated crises, as well as how different causes impose different ways in which countries act in suppressing the consequences.